Tracing the Winds: A Uniform Interpretation of Helium Escape in Exoplanets from Archival Spectroscopic Observations - Patrick McCreery; Leonardo A. Dos Santos; Néstor Espinoza; Romain Allart; James Kirk (The Astrophysical Journal)
Over the past decade, observations of evaporating exoplanets have become increasingly common, driven by the discovery of the near-infrared helium-triplet line as a powerful probe of atmospheric escape. This process significantly influences the evolution of exoplanets, particularly those smaller than Jupiter. Both theoretical and observational studies have aimed to determine how efficiently exoplanets convert their host star's X-ray and ultraviolet (XUV) radiation into atmospheric mass loss. In this study, we employ the open-source atmospheric escape model p-winds to systematically analyze all publicly available helium triplet spectroscopic detections related to exoplanetary atmospheric escape. Our findings indicate that the retrieved outflows strongly depend on the ratio of XUV flux to planetary density ( F _XUV / ρ _p ), supporting the theoretical framework of energy-limited mass loss. We constrain population-level photoevaporative efficiencies to 0.34 ± 0.13 and 0.75 ± 0.21 for hydrogen-helium fractions of 0.90 and 0.99, respectively. These results offer new insights into exoplanetary atmospheric evolution and will aid future studies on exoplanet population demographics.